Pre-operative and post-operative audiological assessment in cleft lip and palate patients-a prospective study - Priyanka Acharya; B.A. Sahana; Anil Desai; Roshan R. Jalisatgi; Niranjan Kumar (Elsevier, 2021)
Purpose: To assess association of audiological defects in cleft lip and palate (CLP) following two stage cheiloplasty and palatoplasty using clinical evaluation and otoscopy and effect of the surgical repair at an interval of one year. Materials and methods: A pilot research study was performed on sixty CLP patients of 1-6 years of age reporting at Craniofacial & Research Centre, Dharwad, India between October 2016 to October 2018.Subjects were assessed based on history, clinical examination and otoscopy for audiometric defects including Serous otitis media (SOM), retraction pockets, impacted wax pre-palatoplasty and findings were compared with control group. Study group were followed up postoperatively at 1, 3, 6 and 12 months and statistical analysis was carried. Results: Higher incidence of conductive audiological defects were noted in study group (96.6%) to control group (8.33%). Of the sixty cleft patients subjected to screening otoscopy, 58 subjects had significant findings like serous otitis media(12.07%), retraction pockets(23.14%), impacted wax(62.04%), bulging of tympanic membrane(3.45%) which were clinically unnoticed. Post palatoplasty no changes were noted at 1 and 3 months, however at 6- and 12months significant improvement was noted (55.17%), with three subjects lost to follow up (6.90%) and none presenting with permanent deafness.results. Conclusion: Cleft anomalies occur in different degrees of severity and configuration with greater incidence of conductive hearing defects of 97%. Positive correlation was noted in cleft palate cases with significant improvement after palatoplasty at an earlier age. However, future long term studies are warranted for long term assessment of Eustachian tube function.conclusion.